Persepsi Pemuda Terhadap Kepemimpinan Politisi Partai Aceh di Lembaga Eksekutif dan Legislatif - Munawar, Munawar (Al-Ijtima`i: International Journal of Government and Social Science, 2017)
Aceh Party is one of local political party which listed on Aceh Government Constitution (UUPA) Number 11, 2006 about Local Political Party. The leadership of Executive and Legislative Institution was being controlled by Aceh Party politicians since 2009 to present, thus raising various perceptions of society and youth in particular to the leadership of Aceh Party. Theory of Symbolic Interactionism is used to analyze the problems in this thesis. The study aimed to determine the youth perception to the leadership of Aceh Party politicians in Executive and Legislative. The study was using descriptive qualitative method. The datas were collected by the interview and documentation. The results show that the leadership of Aceh Party politicians in the executive and legislative has not been in line with the expectations of the Acehnese, because they have not been able to solve the problems that occur, such as poverty, unemployment, and public prosperity. On the other hand, Aceh gained special autonomy which has large budgets. The leadership of the Aceh Party politicians must be able to bring the change towards a better, productive, open not exclusive, and focus on the public prosperity, and also objectify the points which listed on Aceh Government Constitution Number 11, 2006.